2016
DOI: 10.1016/j.jiph.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of hepatitis C knowledge and correlations with health belief model constructs among African American “baby boomers”

Abstract: Overall, respondents have a low level of knowledge. The lower level of education and older age were significant predictors of inadequate HCV knowledge. Thus, HCV education among these people may be a vital component in reducing the gaps in HCV knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…Previous studies have shown that patients with HCV have low funds of knowledge about the virus and its treatment, which is consistent with findings from the current study[1719]. …”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that patients with HCV have low funds of knowledge about the virus and its treatment, which is consistent with findings from the current study[1719]. …”
Section: Discussionsupporting
confidence: 93%
“…Ten studies reported information on knowledge of HCV transmission among the general public (8,(10)(11)(12)(14)(15)(16)(17)19,21). One Canadian study reported that the most frequently known HCV transmission routes were blood transfusions, unsafe/ unprotected intercourse and injection drug use/sharing of needles (14).…”
Section: Knowledge Of Transmissionmentioning
confidence: 99%
“…Furthermore, approximately 54-62% of the general population in Canada knew that HCV is transmitted mainly through blood-to- Abbreviations: HCV, hepatitis C virus; HIV, human immunodeficiency virus a Some studies included more than one population or country blood contact (16). In four studies, a small percentage of the general public indicated that HCV can be transmitted through kissing or casual contact (8,12,14,21).…”
Section: Knowledge Of Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs, environ 54 à 62 % de la population canadienne savait que le VHC se transmet principalement par contact direct de sang à sang (16). Dans quatre études, un petit pourcentage de la population en général a indiqué que le VHC peut être transmis par un baiser ou par simple contact (8,12,14,21).…”
Section: Connaissance De La Transmissionunclassified